2011
DOI: 10.1152/ajpcell.00135.2010
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Kir2 potassium channels to ATP-induced cell death in brain capillary endothelial cells and reconstructed HEK293 cell model

Abstract: ]i rise induced membrane hyperpolarization via the activation of apamin-sensitive small-conductance Ca 2ϩ -activated K ϩ channels (SK2) and enhanced cell proliferation in t-BBEC 117. Here, we found anomalous membrane hyperpolarization lasting for over 10 min in response to ATP in ϳ15% of t-BBEC 117, in which inward rectifier K ϩ channel (Kir2.1) was extensively expressed. Once anomalous hyperpolarization was triggered by ATP, it was removed by Ba 2ϩ but not by apamin. Prolonged exposure to ATP␥S increased the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…-insensitive component of membrane hyperpolarization induced by SOCE was also blocked by 100 nM UCL1684 (normal: 0.66 ± 0.014 tunicamycin: 0.70 ± 0.019, n = 23 and 33 respectively, P = 0.17) (data not shown) and is supposed to be due to SK2 channel activation as has been suggested in the previous reports (5,8). The membrane hyperpolarization caused an increase of Kir2.1 conductance in t-BBEC117.…”
Section: Short Communicationsupporting
confidence: 74%
See 4 more Smart Citations
“…-insensitive component of membrane hyperpolarization induced by SOCE was also blocked by 100 nM UCL1684 (normal: 0.66 ± 0.014 tunicamycin: 0.70 ± 0.019, n = 23 and 33 respectively, P = 0.17) (data not shown) and is supposed to be due to SK2 channel activation as has been suggested in the previous reports (5,8). The membrane hyperpolarization caused an increase of Kir2.1 conductance in t-BBEC117.…”
Section: Short Communicationsupporting
confidence: 74%
“…The membrane hyperpolarization caused an increase of Kir2.1 conductance in t-BBEC117. The excessive membrane hyperpolarization mediated by SK2 and Kir2.1 channels induced further Ca 2+ entry (5,8). These results indicated that Ca 2+ influx in ER stressloaded cells sequentially activated SK2 and Kir2.1 channels, and the subsequent membrane hyperpolarization induced further Ca 2+ entry.…”
Section: Short Communicationmentioning
confidence: 82%
See 3 more Smart Citations